Influence of thickness on the drying of papaya puree (carica papaya l.) through refractance windowtm technology (2013)
The aim of this study was to evaluate the influence of sample thickness (2, 3 and 4 mm) on the drying kinetics, water activity (aw) and color (DE) of papaya puree slices processed through Refractance WindowTM technology (RWTM). Additionally, the water diffusion coefficient (Deff) was evaluated taking into account the shrinkage effect. The experimental values of moisture were fitted using Newton's and Midilli’s models. The results showed that the lower the thickness, the faster the drying, the lower the values of aw and the higher the DE. The samples reached 0.0652, 0.1132 and 0.2624 g water/ g dry solid in 60 min for 2, 3 and 4 mm slices, respectively. Midilli's model was the most appropriate to predict the experimental curves of papaya drying through RWTM. Deff decreased at a lower thickness and its order of magnitude was of 10-10 m2/s.